1997
DOI: 10.1021/es960928k
|View full text |Cite
|
Sign up to set email alerts
|

Desorption of [14C]Naphthalene from Bioremediated and Nonbioremediated Soils Contaminated with Creosote Compounds

Abstract: Bioremediation changes the quantity and nature of the contaminant matrix remaining in soil, because some compounds are selectively degraded while others remain undegraded. It was hypothesized that changes to the contaminant matrix may alter the chemical and physical properties of the soil, such that subsequent desorption of a specific PAH compound would be altered. Desorption of [14C]naphthalene from two creosote-contaminated soils was measured before and after bioremediation. Although the bioremediation treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Scanning-electron microscopic images reveal that primary particle sizes of Fisher lampblack are in the range of tens to hundreds of nanometers. Given the specific density of 1.3 to 1.7 g/cm 3 , the BET surface area measured by N 2 adsorption appears to be not much greater than the calculated exterior surface area of lampblack spherical particles-for example, 18 to 23 m 2 /g, assuming an average diameter of 100 nm and the specific density from 1.3 to 1.7 g/cm 3 . These results suggest that lampblack has a condensed structure, with pores Availability of PAHs in oil-gas plant site soils Environ.…”
Section: Characterization Of Tar-spiked Lampblackmentioning
confidence: 77%
See 1 more Smart Citation
“…Scanning-electron microscopic images reveal that primary particle sizes of Fisher lampblack are in the range of tens to hundreds of nanometers. Given the specific density of 1.3 to 1.7 g/cm 3 , the BET surface area measured by N 2 adsorption appears to be not much greater than the calculated exterior surface area of lampblack spherical particles-for example, 18 to 23 m 2 /g, assuming an average diameter of 100 nm and the specific density from 1.3 to 1.7 g/cm 3 . These results suggest that lampblack has a condensed structure, with pores Availability of PAHs in oil-gas plant site soils Environ.…”
Section: Characterization Of Tar-spiked Lampblackmentioning
confidence: 77%
“…The main sources of polycyclic aromatic hydrocarbons (PAHs) in the environment include incomplete combustion processes of fossil fuels and biomass as well as direct spills of oil and petroleum products. High levels of PAHs often are found in soils or sediments in the proximity of oil and coal gasification processes (former manufactured gas plants) [1,2], tar factories, and wood‐preserving facilities [3]. Numerous studies show that sorption of PAHs to soils and sediments is a fundamental process in modeling the transport of these organic compounds in the environment and also for assessing PAH ecotoxicological risks and developing site‐remediation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, fresh oils were shown to cause so-called "cosolvent effects" (i.e., enhancement of aqueous solubilities of HOCs by water accommodated oil fractions), lowering apparent soil-water distribution coefficients (8,9). In contrast, in soil samples from the field, weathered oil residues did appear to behave as an additional sorption phase (10)(11)(12)(13)(14)(15), reducing aqueous concentrations (13,14) and thus lowering bioavailability and biodegradation (11). This is in line with expectations because the light, water-soluble oil fractions responsible for solubility enhancement of HOCs usually get washed away or degrade during natural weathering of oil (16), leaving only the nonsoluble so-called "unresolved complex mixture" (UCM) (17).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced bioavailability may arise from sorption onto residual NAPL phase with a higher K oc . We are not confident that happened because Rutherford et al (1997) showed that the partition coefficient of naphthalene onto creosote was relatively insensitive to creosote source or bioremediation. We believe this low bioavailability might relate to prior history, texture and structure.…”
Section: Bioavailability Of Contaminants After Agingmentioning
confidence: 96%